The Comparison of the use Of Talc 76% Iso With 80% ISO for Pitch Reduction in The D0 Stage Pulp Bleaching Process - Susantini, Ni Njoman Manik; Linda Ardiyana (Journal of Scientific Insights, 2025)
One of the problems that occur in pulp and paper mills is the problem of pitch content. The addition of talc chemicals in the D0 stage bleaching process is known to reduce the pitch content in the pulp. This study aims to determine the effectiveness of talc 76% ISO and Talc 80% ISO in reducing the pitch content in the D0 stage bleaching pulp and to determine the quality of the D0 pulp produced after the addition of the two types of talc. In this experiment, Talc 76% ISO and Talc 80% ISO were added and varied the addition of chlorine dioxide to the pre-D0 pulp, then the DO stage bleaching was carried out. The research method used was a testing method by examining the quality parameters of the D0 pulp, namely brightness, residual lignin content, viscosity, and pitch content. Based on the experiments carried out, it was concluded that Talc 80% ISO was more effective than Talc 76% ISO in reducing the pitch content in D0 pulp, with a reduction efficiency of Talc 76% ISO of 14.2% and Talc 80% ISO of 41.6%. And based on the comparison of data processing results, the comparison results of the quality of D0 pulp produced between the two types of talc are not very significant, so this cannot prove the author's hypothesis which states that the quality of D0 pulp in samples using 80% ISO Talc is better than samples using talc 76% ISO.